Plasma Free Fatty Acids and Risk of Heart Failure: The Cardiovascular Health Study - Djoussé, Luc (2013)
BACKGROUND: Although plasma free fatty acid (FFA) concentrations have been associated with lipotoxicity, apoptosis, and risk of diabetes and coronary heart disease, it is unclear whether FFA levels are associated with heart failure (HF). METHODS AND RESULTS: To test the hypothesis that plasma concentration of FFA is positively associated with incident HF, we prospectively analyzed data on 4248 men and women free of HF at baseline and aged 65+ years from the Cardiovascular Health Study. FFA concentration was measured in duplicate by the Wako enzymatic method. Incident HF was validated by a centralized Events Committee. We used Cox proportional hazards to estimate the hazard ratio of HF per standard deviation (SD) of FFA. During a median follow up of 10.5 y, 1,286 new cases of HF occurred. In a multivariable model adjusting for clinic site, comorbidity, demographic, anthropometric, and lifestyle factors, each SD (0.2 mEq/L) higher plasma FFA was associated with 12% (95% CI: 6% to 19%) higher risk of HF. Controlling for time-varying diabetes and coronary heart disease did not change the results [HR per SD: 1.16 (95% CI: 1.09–1.23)]. CONCLUSIONS: A single measure of plasma FFA obtained later in life is associated with a higher risk of HF in older adults. Additional studies are needed to explore biologic mechanisms by which FFA may influence the risk of HF and determine whether FFA could serve as a novel pharmacological target for HF prevention.